Bone augmentation using autogenous bone versus biomaterial in the posterior region of atrophic mandibles: A systematic review and meta-analysis - Sousa, Cecilia Alves de [UNESP]; Araujo Lemos, Cleidiel Aparecido [UNESP]; Santiago-Junior, Joel Ferreira; Faverani, Leonardo Perez [UNESP]; Pellizzer, Eduardo Piza [UNESP] (Elsevier B.V., 2018)
Objectives: This systematic review and meta-analysis aimed to answer the PICO question: Do patients who have received bone grafts with bone substitute (biomaterials) present bone gain (before implant installation), complications, and implant survival rates similar to autogenous grafts when used in the posterior mandible region?. Data: This review followed the PRISMA statement and has been registered at PROSPERO (CRD42016048471). Studies published in English, randomized controlled and/or prospective clinical trials with at least 10 patients, and studies that compared grafts with bone substitutes to autogenous bone grafts (split-mouth design) were included. Sources: An electronic search and a manual search were conducted in PubMed/MEDLINE, Scopus, and Cochrane databases up to April 2018. Study selection: Our initial search yielded 640 articles; we selected four articles that met the inclusion criteria. All selected studies used a split-mouth design. Results: Our analysis revealed no significant difference between the biomaterial and autogenous groups in terms of bone gain (P = 0.11; mean difference [MD]: 0.59; 95% confidence interval [CI]: -0.13-1.31) or complication rate (P = 0.72; risk ratio [RR]: 1.25; 95% CI: 0.37-4.23). Sixty-six implants were installed in the biomaterial group and 63 in the autogenous group; these showed no significant difference in implant survival rate (P = 0.50; RR: 1.57; 95% CI: 0.43-5.81). Conclusion: We conclude that biomaterials or autogenous bone are indicated for the reconstruction of the posterior mandibular atrophic region, without lowering implant survival.
Keywords: Bone grafting; Mandible; Dental implants